Parkin deficiency delays motor decline and disease manifestation in a mouse model of synucleinopathy. - Margot Fournier (PLoS ONE, 2009)
In synucleinopathies, including Parkinson's disease, partially ubiquitylated alpha-synuclein species phosphorylated on serine 129 (P(S129)-alpha-synuclein) accumulate abnormally. Parkin, an ubiquitin-protein ligase that is dysfunctional in autosomal recessive parkinsonism, protects against alpha-synuclein-mediated toxicity in various models.We analyzed the effects of Parkin deficiency in a mouse model of synucleinopathy to explore the possibility that Parkin and alpha-synuclein act in the same biochemical pathway. Whether or not Parkin was present, these mice developed an age-dependent neurodegenerative disorder preceded by a progressive decline in performance in tasks predictive of sensorimotor dysfunction. The symptoms were accompanied by the deposition of P(S129)-alpha-synuclein but not P(S87)-alpha-synuclein in neuronal cell bodies and neuritic processes throughout the brainstem and the spinal cord; activation of caspase 9 was observed in 5% of the P(S129)-alpha-synuclein-positive neurons. As in Lewy bodies, ubiquitin-immunoreactivity, albeit less abundant, was invariably co-localized with P(S129)-alpha-synuclein. During late disease stages, the disease-specific neuropathological features revealed by ubiquitin- and P(S129)-alpha-synuclein-specific antibodies were similar in mice with or without Parkin. However, the proportion of P(S129)-alpha-synuclein-immunoreactive neuronal cell bodies and neurites co-stained for ubiquitin was lower in the absence than in the presence of Parkin, suggesting less advanced synucleinopathy. Moreover, sensorimotor impairment and manifestation of the neurodegenerative phenotype due to overproduction of human alpha-synuclein were significantly delayed in Parkin-deficient mice.These findings raise the possibility that effective compensatory mechanisms modulate the phenotypic expression of disease in parkin-related parkinsonism.